On the Possibility of Life after Limbo: A Commentary on Knowledge, Institutions and Society in Eastern Europe Since the Demise of Communism - Voldemar Tomusk (Les éditions de la Maison des sciences de l'Homme, 2006)
In this article an attempt is being made to place post-communist higher education in broader social, economic and political contexts. It is argued that contrary to popular views that relate the expansion of higher education enrolment to growing knowledge intensive sectors of the economy, mass higher education functions in the region as low-cost buffer of social tensions caused by the economic restructuring and instability. It is argued that significant continuities exist between the communist and post-communist societies, perpetuated in particular by the social institutions produced and reproduced in higher education. As long as these institutions remain primarily symbols and ceremonies devoid of academic and professional substance, higher living standards in the new economy of Eastern Europe will not be reached.